2018
DOI: 10.20448/journal.506.2018.51.22.26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Long Term Irrigation by Treated Effluent on Boron Accumulation in Soil and Citrus Plants

Abstract: The aim of the current research is to assess the long term effect of boron concentration in treated wastewater on citrus plants cultivated in various soil textures. Boron concentrations of treated wastewater used in sandy and clay soil were 1.45±0.37 and 1.03±0.45 mg/l, respectively. In sandy soil, Boron concentrations were 0.53 ± 0.15 and 3.94 ± 0.97 mg/ kg soil showed significant variation at p < 0.05 between the top 0-30 and the second layer 30-60 cm, respectively, while the leaves of citrus have boron conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The B 3+ concentration in the irrigation waters exceed the maximum threshold proposed for citrus [4,31] (0.5 mg/L; Table 1). In this context, Abu-Daba'an and Al-Najar [38] irrigated a citrus orchard for ten consecutive years with a treated effluent with a B 3+ concentration of 1.03 ± 0.45 mg/L and did not reach toxic levels for B 3+ leaf concentration. However, they also concluded that, since B 3+ is accumulative, if the same irrigation water is used for 30 years, leaf B 3+ concentrations could reach that harmful level.…”
Section: Leaf Mineral Analysis and Phytotoxic Elementsmentioning
confidence: 99%
“…The B 3+ concentration in the irrigation waters exceed the maximum threshold proposed for citrus [4,31] (0.5 mg/L; Table 1). In this context, Abu-Daba'an and Al-Najar [38] irrigated a citrus orchard for ten consecutive years with a treated effluent with a B 3+ concentration of 1.03 ± 0.45 mg/L and did not reach toxic levels for B 3+ leaf concentration. However, they also concluded that, since B 3+ is accumulative, if the same irrigation water is used for 30 years, leaf B 3+ concentrations could reach that harmful level.…”
Section: Leaf Mineral Analysis and Phytotoxic Elementsmentioning
confidence: 99%
“…Recycled wastewater contains a significant level of sodium and boron (Feigin, Ravina, & Shalhevet, 1991;Rehman & Cheema, 2017;Abu Daba' & Al-Najar, 2018), affecting its use for irrigation, especially for sensitive plants. Such ions are potentially harmful to plants, and crop production and long-term soil sustainability can be jeopardized without effective soil and water management.…”
Section: Introductionmentioning
confidence: 99%
“…Boron and NaCl are commonly found in irrigation water (Abu-Sharar, Hani, & Al-Khader, 2014;Abu Daba' & Al-Najar, 2018). The aim of this research is to determine whether the presence of both boron and NaCl in water in high concentrations inhibits the germination and growth of wheat seedlings or to determine if one factor has an antagonistic relationship with the other.…”
Section: Introductionmentioning
confidence: 99%